Analysis of cis-acting regulatory elements of Respiratory burst oxidase homolog (Rboh) gene families in Arabidopsis and rice provides clues for their diverse functions. (June 2016) - Kaur, Gurpreet; Pati, Pratap Kumar
Graphical abstract: Highlights: First time an in silico promoter analysis of Rboh genes from Arabidopsis and rice. Distribution of cis-acting elements, CpG islands and tandem repeats are analyzed. Key elements in Rbohs promoter are indicated accounting their functional diversity. Validation of in silico data with the experimental evidence where ever available. Abstract: NADPH oxidase (NOX) is a critical enzyme in the production of reactive oxygen species (ROS). It catalyzes the production of apoplastic superoxide (O2 − ), that regulates a wide array of biological functions in different organisms. Plant Noxes are homologs of catalytic subunit of mammalian NADPH oxidase and are well-known as Respiratory burst oxidase homologs (Rbohs). In recent years, there has been growing interest to study plant Noxes due to their versatile roles in plant systems. In the present work, comprehensive analysis on upstream regions from 10 Rbohs from Arabidopsis thaliana and 9 from Oryza sativa japonica was conducted. The distribution of various cis-elements, CpG islands and tandem repeats were analyzed to uncover the 5′ regulatory region in wide array of functions from Rbohs . Information retrieved from cis-elements analysis was also correlated with the microarray data. Present study which involves uncovering transcription regulatory elements provided vital clues for diverse functions of plant Rbohs.